Пожалуйста помогите срочно как сможете
1) 2^x+2 - 2^x+1 + 2^x-1 - 2^x-2<=9
2) 3^2x-1 + 3^2x-2 - 3^2x-4<= 315
3) 2^x - 2^x-4>15

1) 25^x < 6*5^x - 5
2) 3^2x - 3*2^x + 2>0
3) 4^x + 2^x+3 > 20
4) 2^2x - 3*2^x + 2> 0

2
2) 3^2х-1 + 3^2х-2 -3^2х-4<=315; 3^2х/3 - 3^2х/3^2 - 3^2х/3^4<=315; 3^2х*(27+9-1)/81<=315; 3^2х<=315*81/35; 3^2х<=729; 3^2х<=3^6; 2х<=6; х<=3
3)2^х - 2^х-4 > 15; 2^х - 2^х/2^4 > 15; 2^х*(16-1)/16 > 15; 2^х > 15*16/15; 2^х > 16; 2^х > 2^4; х > 4

Ответы и объяснения

Лучший Ответ!
2014-02-05T16:11:04+04:00
1)2^х+2 - 2^х+1 + 2^х-1 - 2^х-2<=9
2^х*2^2 - 2^х*2 + 2^х/2 - 2^х/2^2<=9
2^х(4-2+1/2-1/4)<=9
2^х * 2 1/4<=9
2^х<=4
2^х<=2^2
х<=2
2014-02-05T18:21:06+04:00
1)  2^{x+2}- 2^{x-1}+ 2^{x-1}- 2^{x-2} \leq 9
 2^{x}*4- 2^{x}*2+ \frac{ 2^{x} }{2}- \frac{ 2^{x} }{4} \leq 9
 2^{x}(4-2+ \frac{1}{2}- \frac{1}{4}) \leq 9
 2^{x}* \frac{9}{4} \leq 9
 2^{x} \leq 4
 2^{x} \leq  2^{2}
x≤2
2)  3^{2x-1}+ 3^{2x-2}- 3^{2x-4} \leq 315
 \frac{ 3^{2x} }{3} + \frac{ 3^{2x} }{9} - \frac{ 3^{2x} }{81}  \leq 315
 3^{2x} ( \frac{1}{3} + \frac{1}{9} + \frac{1}{81} ) \leq 315
 3^{2x}* \frac{35}{81} \leq 315
 3^{2x} \leq 729
 3^{2x} \leq  3^{6}
2x≤6
x≤3
3)  2^{x}- 2^{x-4}  >15
 2^{x}- \frac{ 2^{x} }{16}>15
 2^{x}(1- \frac{1}{16})>15
 2^{x}>16
x>4

1)  25^{x}<6* 5^{x}-5
 5^{2x}-6* 5^{x}+5<0
 5^{x}=t; t>0
 \left \{ {{ t^{2}-6t+5<0} \atop {t>0}} \right.
t² - 6t + 5 < 0
t₁ = 1
t₂ = 5
t∈ (1;5), т.е.
1<t<5
 \left \{ {{t>1} \atop {t<5}} \right.
 \left \{ {{ 5^{x}>1 } \atop { 5^{x}<5 }} \right.
 \left \{ {{x>0} \atop {x<1}} \right.
x∈ (0;1)
3)  4^{x}+ 2^{x+3}>20
 2^{2x}+ 2^{x}*8 -20>0
 2^{x}=t; t>0
 \left \{ {{ t^{2}+8t-20>0 } \atop {t>0}} \right.
t² + 8t - 20 >0
D₁ = 16 + 20 = 36
t₁ = -4+6 = 2
t₂ = -4-6 = -10
t∈ (-беск.;-10)U(2;+беск.), но так как t>0, то
t∈ (2; + беск.) или t>2
 2^{x} >2
x>1
4)  2^{2x}-3* 2^{x}+2>0
 2^{x}=t; t>0
 \left \{ {{ t^{2}-3t+2>0 } \atop {t>0}} \right.
t² - 3t + 2 >0
t₁ = 1
t₂ = 2
t ∈ (-беск.; 1)U(2;+беск.)
так как t>0, то
t ∈ (0;1) U (2; + беск.) или:
 \left \{ {{ 2^{x}<1 } \atop { 2^{x}>2 }} \right.
 \left \{ {{x<0} \atop {x>1}} \right.
x ∈ (-беск.;0) U (1;+беск.)